The Influence of Fundamental Factors, Technical Factors, and Risks Systematic of Stock Prices in Sectors Index Banking Infobank15 Listed On the Indonesia Stock Exchange 2015-2018 Period - Syafira Mariana; Tianna Fenny (Journal of Business, Accounting and Finance, 2022)
The purpose of this study is to determine: 1) The influence of fundamental factors, namely ROA (Return On Asset), ROE (Return On Equity), Debt to Equity Ratio (DER) and CR (Current Ratio) on stock prices in a banking sector, Infobank Index15 registered on the IDX in 2015-2018; 2) The influence of technical factors in the form of trends on stock prices in Banking sector Infobank15 Index listed on the IDX in 2015-2018; 3) The Effect of Systemic Risk (Î²) on stock prices in Banking sector Infobank15 Index listed on the IDX in 2015-2018. The population in this study encloses 15 companies in the Financial and Banking Sector in Infobank15 Index, as many as 15 companies from 2015 to 2018. Infobank15 Index measures the price performance of 15 banking stocks that have good fundamental factors and high trading liquidity. All members of the population are sampled in this study. Therefore, this research is a census research, sampling saturated. The results show that ROA (Return On Asset), ROE (Return On Equity), Debt to Equity Ratio (DER) and CR (Current Ratio) have no effect on stock prices in companies listed in Infobanks Index15. Stock trends have an effect on stock prices in companies listed in the Infobanks15 Index. Systemic risk as measured by stock beta has no effect on the stock price of companies listed in the Infobanks15 Index